Unmet contraception need among married women in somalia: Findings from the first national health and demographic survey - Md Badsha Alam; Md Arif Billah; Shimlin Jahan Khanam; Ibrahim Yasin Khalif; Md Nuruzzaman Khan (PLoS ONE, 2025)
Background Somalia has one of the highest rates of maternal and child mortality globally, accompanied by a significantly high total fertility rate. This indicates that women in Somalia face substantial challenges in accessing family planning and contraception, although evidence on this issue remains limited. This study aims to assess the current prevalence of unmet need for contraception in Somalia and identify the socio-demographic factors associated with it. Methods A total of 7,490 sexually active women of reproductive age with the ability to conceive were included in this study, based on pre-defined inclusion criteria, using data from the 2020 Somalia Health and Demographic Survey. The primary outcome variable was unmet need for contraception (yes/no), which included both unmet need for spacing and limiting births. A range of individual, household, and community-level variables were examined as explanatory factors. Multilevel logistic regression models were used to assess the associations between these factors and unmet need for contraception. Results The overall prevalence of unmet need for contraception was 37.2% (95% CI: 35.3–39.1), with significant variations across socio-demographic groups. Women who married at age 21 or older (aOR: 1.25; 95% CI: 1.03–1.51), had five or more children (aOR: 2.41; 95% CI: 2.00–2.89), or lived in the central (aOR: 1.36; 95% CI: 1.05–1.76) and southern regions (aOR: 1.59; 95% CI: 1.00–2.54) were more likely to have an unmet need for contraception. In contrast, women aged 35 or older (aOR: 0.59; 95% CI: 0.43–0.79), and those residing in urban (aOR: 0.71; 95% CI: 0.52–0.98) and rural areas (aOR: 0.77; 95% CI: 0.59–0.99) were less likely to have an unmet need. Conclusion The prevalence of unmet need for contraception in Somalia is alarmingly high by global standards. This reflects a heightened risk of short birth intervals and unintended pregnancies, contributing to increased maternal and child mortality. To address this, the government should prioritize strengthening healthcare infrastructure and implementing targeted awareness programs on family planning to reduce the unmet need for contraception in the country.